226 Mile Lonnie Bedwell Blind Adventure : Grand Canyon Adventure - Bedwell Lonnie (Pro Player Publishing, 2015)
This book storied Lonnie Bedwell, the first blind kayaker to run the entire length of the Grand Canyon in a solo kayak, epitomize courage and devotion in this historic achievement